Interfaith Marriage And The Dilemma Of National Legal: A Comparative Analysis Of Religious Identity And Human Rights - Kurniasih, Uun; Kosim, Kosim; Setyawan, Edy (PPPM, Sekolah Tinggi Ilmu Hukum (STIH) Biak-Papua, 2026)
The Indonesian law on interfaith marriage does not explicitly prohibit it, but it also lacks clear legal clarity, leading to confusion and gaps in its implementation. This study employed a qualitative, literature-based research method based on both legislative and comparative approaches. This study compares Indonesia's legal approach with other countries, based on existing laws and community practices. The legal vacuum surrounding interfaith marriage often leads Indonesians to circumvent domestic legal limitations by marrying abroad and re-registering them in Indonesia. Another approach is to marry twice, with each bride and groom representing their respective religions. This reflects the inability of national law to accommodate increasingly pluralistic and cross-border social realities. Strong religious identities, such as Malaysia, explicitly prohibit interfaith marriage through its Islamic family law framework. Conversely, countries with high levels of religious tolerance and strong cultural ties, such as Ethiopia, the United Kingdom, and Singapore, tend to allow freedom of interfaith marriage on the basis of human rights. Indonesian legal policy needs reform to provide legal clarity and be based on community culture, so that community attempts to circumvent the law can be overcome.